What Is the Long-Term Clinical Efficacy of the Thoraflex™ Hybrid Prosthesis for Aortic Arch Repair? - Tan, Sven Z. C. P.; Jubouri, Matti; Mohammed, Idhrees; Bashir, Mohamad (Frontiers in Cardiovascular Medicine, 2022)
Background: The widespread adoption of the frozen elephant trunk (FET) technique for total arch reconstruction (TAR) in aortic arch aneurysm and dissection has led to the development of numerous commercial single-piece FET devices, each with its own unique design features. One such device, Thoraflex™ Hybrid (Terumo Aortic, Glasgow, Scotland), has enjoyed widespread use since its introduction. We present and appraisal of its long-term clinical efficacy, based on international data. Materials and Methods: Pre-, intra-, and postoperative data associated with Thoraflex™ Hybrid implantations for aortic arch dissection, aneurysm, and penetrating atherosclerotic ulcer (PAU) up to April 2019 was gathered and is presented herein. Follow-up data at discharge, 3-, 6-, 12-, 24-, 36-, 48-, 60-, 72-, and 84- months post-implantation are included. Results: Data associated with 931 cases of Thoraflex™ Hybrid implantation are included. Mean age at implantation was 63 ±12 years. 55% of patients included were male. Aortic dissection accounted for 48% (n=464) of cases. Mean cardiopulmonary bypass and circulatory arrest durations were 202 +72 and 69 ±50 min respectively. 30-day mortality was 0.6% (n=6), while overall mortality was 14 (1.5%). Freedom from adverse events at 84 months was 95% (n=869). Postoperative complications included neurological deficit, multi-organ failure, cardiorespiratory compromise, and infection. Discussion: Thoraflex™ Hybrid’s unique design is advantageous in comparison to market alternatives. Our data is consistent with that reported in literature and suggests Thoraflex™ Hybrid is associated with favourable rates of mortality and morbidity. Conclusion: Thoraflex™ Hybrid remains a central player in the aortic arch prosthesis market. Its use it widespread and is associated with favourable design features and clinical outcomes relative to market alternatives.